The effect of service quality, facilities, atmosphere, and short waiting time on hemodialysis patient satisfaction - Hermanto, Amanda (Enrichment : Journal of Management, 2024)
The purpose of this study is to examine the impact of service quality, facilities, atmosphere, and wait time management on the satisfaction of hemodialysis patients at XYZ Hospital in Tangerang City. This is a quantitative study with a cross- sectional design and the sampling method used is census. Empirical data obtained from May to June 2024 through online questionnaires with 152 hemodialysis patients who had been receiving treatment for at least one year. The data were processed and analyzed using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) path, higher-order construct, the disjoint two- stage approach using the SmartPLS 4 program.The study results indicate that all four tested factors, namely service quality, facilities, atmosphere, and short waiting time, have a positive on patient satisfaction